Cicero and the ’Insatiable Variety’ of Nature in Book II of De natura deorum - Degl’Innocenti Pierini, Rita (Ciceroniana On Line, 2023)
The article studies the exaltation of the manifold variety of terrestrial landscapes by the Stoic Balbus in the second book of De natura deorum (98-99). Cicero delivers a highly elaborate and formal description of the insatiabilis varietas of nature, in which natural, even wild, landscapes coexist with “cultural” landscapes, i.e. with evident traces of human intervention. The article examines the probable philosophical ancestry, expressive and poetic components of these landscapes, as well as their Nachleben (particularly in Seneca and Apuleius).